Not my Doctrine? Finding a Contract Law Explanation for Non Est Factum - Connell, Simon (Victoria University of Wellington Law Review, 2016)
Non est factum (Latin for "not my deed") is a common law doctrine that can allow the signer of a legal document to escape the usual legal consequences of their signature. In its early days, non est factum was available only to blind and illiterate persons who, without being careless, relied on another party’s seriously flawed explanation of the document. Non est factum can void contracts, but I argue the general explanation for the doctrine is not a satisfactory explanation for why it applies to contracts. This article considers whether there is an explanation for non est factum that is consistent with contract law thinking. I argue that there is, and explain non est factum as an application of the objective principle set out in Smith v Hughes.